Loss of ATRX suppresses ATM dependent DNA damage repair by modulating H3K9me3 to enhance temozolomide sensitivity in glioma. (10th April 2018) - Han, Bo; Cai, Jinquan; Gao, Weida; Meng, Xiangqi; Gao, Fei; Wu, Pengfei; Duan, Chunbin; Wang, Ruijia; Dinislam, Magafurov; Lin, Lin; Kang, Chunsheng; Jiang, Chuanlu
Abstract: Mutations in ATRX constitute the most prevalent genetic abnormalities in gliomas. The presence of ATRX mutations in glioma serves as a marker of better prognosis with longer patient survival although the underlying mechanisms are poorly understood. In the present study, we found that ATRX biological function was significantly involved in DNA replication and repair. CRISPR/Cas9-mediated genetic inactivation of ATRX induced inhibition of cell proliferation, invasion and vasculogenic mimicry. In addition, temozolomide (TMZ) treatment induced greater DNA damage and apoptotic changes in ATRX knockout glioma cells. Moreover, we confirmed that ATRX knockout resulted in a failure to trigger ATM phosphorylation and finally restrained the activation of downstream proteins of the ATM pathway. The ATM-associated DNA repair pathway was extensively compromised in ATRX knockout cells owing to decreased histone H3K9me3 availability. Public databases also showed that patients with low ATRX expression exhibited preferable overall survival and profited more from TMZ treatment. These data suggest that ATRX is involved in DNA damage repair by regulating the ATM pathway and might serve as a prognostic maker in predicting TMZ chemosensitivity. Highlights: ATRX knockout downregulates glioma cell malignant behaviors. ATRX regulates DNA damage repair through the ATM signaling pathway. ATRX expression correlates with the chemosensitivity of patients with GBM.